1938
DOI: 10.1177/003591573803101112
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Pathology of Ménière's Syndrome

Abstract: IT is the purpose of this paper to describe-as is believed, for the first time-the pathological changes in the temporal bones in two cases of Meniere's syndrome. In both death occurred shortly after operation for section of the 8th nerve. For the purposes of the present paper, the surgical factors concerned in the operative failure of these cases will be dealt with only in so far as they are related to the interpretation of the histological changes which are now to be described. Their detailed consideration wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
8

Year Published

1938
1938
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(126 citation statements)
references
References 9 publications
1
117
0
8
Order By: Relevance
“…In all these cases the saccus endolymphaticus is normal and the utriculus full; so that if there were a communication between the saccus and sacculus, the latter might also be expected to fill. The classical picture of Meniere's disease, first reported by Hallpike and Cairns (1938) demonstrates dilatation of the scala media and sacculus but not of the utriculus or semi-circular canals, again strong suggestive evidence that continuity throughout the endolymph system does not always exist. The third condition, seen in an old dog, shows a normal sacculus, scala media, organ of Corti, etc., but an_atrophic, nonsecretory saccus and collapsed utriculus and semicircular canals on both 707 sides.…”
Section: Fig 8 Microphotograph Of Non-vascular Type Of Papilla Showmentioning
confidence: 94%
“…In all these cases the saccus endolymphaticus is normal and the utriculus full; so that if there were a communication between the saccus and sacculus, the latter might also be expected to fill. The classical picture of Meniere's disease, first reported by Hallpike and Cairns (1938) demonstrates dilatation of the scala media and sacculus but not of the utriculus or semi-circular canals, again strong suggestive evidence that continuity throughout the endolymph system does not always exist. The third condition, seen in an old dog, shows a normal sacculus, scala media, organ of Corti, etc., but an_atrophic, nonsecretory saccus and collapsed utriculus and semicircular canals on both 707 sides.…”
Section: Fig 8 Microphotograph Of Non-vascular Type Of Papilla Showmentioning
confidence: 94%
“…For many years, the diagnosis of Menière′s disease was a clinical diagnosis based on recurrent episodes of vertigo, hearing loss, aural fullness and/or tinnitus. The pathologic hallmark of Menière′s disease is endolymphatic hydrops . Recently, the development of MRI and the use of intratympanically applied gadolinium‐based contrast agents have enabled the visualisation of endolymphatic hydrops in living patients .…”
Section: Dear Editormentioning
confidence: 99%
“…In addition to recurrent vertigo, patients with MD have fluctuating hearing loss, tinnitus, and a sensation of aural fullness (6). Histopathological studies of the temporal bone have revealed endolymphatic hydrops in the affected ears (7)(8)(9). Differential diagnosis of MAV from MD is sometimes hard because patients with MAV could have tinnitus and/or aural fullness during vertigo attacks (10), and a controlled study has provided evidence of the association of MD with migraine (11).…”
Section: Introductionmentioning
confidence: 99%